Supportive Psychotherapy and Psychoeducation as a Media for Changing and Convincing Behavior in Clients with Paranoid Schizophrenia - Imam Shofi'i (Proceedings of The ICECRS, 2020)
Schizophrenia is a psychiatric diagnosis that describes mental disorders with character abnormalities in perception or disorders regarding reality. Perception abnormalities can be in the form of disorders in the five senses, usually in the form of auditory hallucinations, paranoia, bizarre delusions, and can also be in the form of speech disorganization and disruption of real social communication. Case. Mr.SA, age 43, came with complaints of rampage to his family and surrounding community for no apparent reason. The patient was treated at Menur General Hospital Surabaya 2 years ago with a similar complaint. Psychiatric status obtained clear awareness, bad insight, blunt affect, auditory hallucinations, visuals, followed by delusions of control, suspicious. Diagnosis of axis I: paranoid schizophrenia, axis II and III: none, axis IV: Primary Support Group (Family) GAF axis scale 20.11 (danger of self-injury / others when entering hospital). Psychopharmaca therapy is chlorpromazine tab 1 x 100 mg, haloperidol tab 3 x 5 mg, and trihexyphenidyl 3 x 2 mg, and psychotherapy that is support. Conclusion The paranoid schizophrenia of this patient is due to work problems